Correlation study between serum uric acid level and cognitive impairment in middle-aged and elderly patients with hypertension: based on an explainable predictive model - Wang, Jiarui; Liao, Hetong; Zheng, Ping; Chen, Qinfen; Lu, Dongxu; Huang, Yihong; Wu, Di; Hu, Jiajia; Du, Juan; Zhang, Xiaoyun (Frontiers in Neurology, 2025)
BackgroundPatients with primary hypertension are always comorbid with hyperuricemia. Serum uric acid exhibits a dual role in cognitive function. Evidence regarding the relationship between uric acid (SUA) and cognitive dysfunction in specific hypertensive patients remains inconsistent.ObjectiveTo develop a predictive model to evaluate the association between serum uric acid level and mild cognitive impairment (MCI) in hypertensive populations.MethodsThis cross-sectional study involved 420 middle-aged and elderly hypertensive patients. Cognitive function was evaluated using MMSE and MoCA. Univariate and multivariate logistic regression, restricted cubic splines (RCS), and SHAP analysis were employed.ResultsIn MCI group, diabetes prevalence, hyperuricemia prevalence, arteriosclerosis prevalence, education level, MMSE score, MoCA score, AD8 score and HbA1c were higher, while weight, BMI, SUA, TC, LDL, Alb, TT3, TSH, and FT3 were lower. After adjusting for confounding factors, it was found that the SUA level (OR = 0.754, 95%CI: 0.578–0.985, 0.038) could still be used as an independent protective factor for MCI. Subgroup analyses indicated effects varied significantly with diabetes history and regular exercise. Shap values showed that SUA is the fifth most related factor, with more significant ones including age, education level, albumin and thyroxin. A nonlinear association was found between SUA and MCI risk, with an inflection point at approximately 450 μmol/L.ConclusionSUA has a certain correlation with MCI in the middle-aged and elderly hypertensive populations. Although SUA is considered as a neuroprotective agent, its neuroprotective function gradually diminishes and may even become detrimental when SUA higher than a threshold. These results suggest maintaining SUA within an optimal range may help mitigate MCI risk in hypertensive populations.